Post-anthesis supplementary irrigation improves grain yield and nutritional quality of drip-irrigated rice (Oryza sativa L.) - Wang, Xiangbin; Zhang, Xinjiang; Liu, Linghui; Liu, Xiaowu; Feng, Guorui; Wang, Juan; Yin, Yong-an; Wei, Changzhou (Frontiers in Plant Science, 2023)
Drip-irrigated rice save about 50% of irrigation water, show a grant prospect in water-saving agriculture, especially in water resource scared area. However, the grain yield and quality of drip-irrigated rice adversely affected. This study investigated the effect of different irrigation strategies on the grain yield and quality of drip-irrigated rice by a field experiment. Four irrigation treatments were set: the whole growing season flooding (FI); the whole growing season normal drip irrigation (DI, soil relative moisture (RSM) was maintained in a range of 90-100%); pre-anthesis drip irrigation and post-anthesis water stress (SAF, the RSM was maintained in a range of 80-90% after anthesis); pre-anthesis drip irrigation and post-anthesis flooding (FAF). The results showed that grain yield, harvest index, seed setting rate and 1000 grain weight in DI and SAF were significantly lower than those in FI and FAF. These parameters had no significant difference between FI and FAF, but were significantly greater in DI than those in SAF. Compared with FI and FAF, the source capacity, source activity time and sink activity of DI and SAF decreased, and the sink-source difference increased. The sink-source difference had a significant negative correlation with rice yield and 1000 grain weight. The activities of ADP-glucose pyrophosphorylase, starch branching enzyme and amylopectin content in grains on the middle panicles in FAF were significantly greater than those in DI and SAF. The SAF increased the amylose/amylopectin ratio and total protein content in grains, but decreased the proportion of glutenin in total protein compared with DI. Supplying irrigation after anthesis of drip-irrigated rice narrowed the difference between sink source in rice plants, increased grain yield and harvest index by 29.2% and 11% compared to DI, increased the water productivity by 19% compared to FI, and improved grain quality of drip-irrigated rice. This research highlighted that post-anthesis sufficient irrigation of drip-irrigated rice plays a positive role in maintaining the source-sink balance. The study also provided a basis for further improving the grain yield and quality of drip-irrigated rice and formulating more efficient rice water-saving cultivation techniques.